2021
DOI: 10.1108/nfs-04-2020-0137
|View full text |Cite
|
Sign up to set email alerts
|

Collective effect of rosemary (Rosmarinus officinalis) and betel (Piper betel) leaves extract on chicken powder incorporated fried chicken vermicelli

Abstract: Purpose The purpose of this study is to develop chicken powder (CP) incorporated fried chicken vermicelli and to evaluate the collective effect of rosemary and betel leaf extracts (RE+BE) in developed products, on the performance of storage study parameters. Design/methodology/approach Two different groups were made from developed products: the first control group without RE+BE incorporated and the second group treated with RE+BE (1:1). Various chemical, microbiological and sensory parameters of both groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Additionally, our analysis demonstrated higher contents of phenolic and flavonoid in the combined extract compared to rosemary and neem alone. This result supports the reported correlation between antioxidant activity, and total phenolic and flavonoid contents in both neem and rosemary extracts, as demonstrated by Sinai et al (2020) 34 . Notably, this study further suggests a synergistic enhancement of the antioxidant potential when the two extracts are combined comparable to Trolox as standard.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, our analysis demonstrated higher contents of phenolic and flavonoid in the combined extract compared to rosemary and neem alone. This result supports the reported correlation between antioxidant activity, and total phenolic and flavonoid contents in both neem and rosemary extracts, as demonstrated by Sinai et al (2020) 34 . Notably, this study further suggests a synergistic enhancement of the antioxidant potential when the two extracts are combined comparable to Trolox as standard.…”
Section: Discussionsupporting
confidence: 92%
“…Due to their concentrations being between 12.5 and 200 µg/ml, the study findings indicated that the PHF had a very strong antioxidant effect. Better antioxidant activity might be seen in the decreased IC50 value (table 4) [44]. The antioxidant activity of PHF proved that the higher the ROH, the IC50 decreased (fig.…”
Section: Antioxidant Activitymentioning
confidence: 87%
“…The rosemary extract analyzed presented different results from those achieved by Martínez et al (2019), who reported 35.95 mg EAG g sample -1 for the content of total phenolic compounds, 88.76% of DPPH radical chelating activity, and 73.43 mg EAG g sample -1 for FRAP in rosemary extract samples with lecithin as an emulsifier. Saini et al (2020) reported 136.66±7.41 mg EAG g sample -1 for the content of phenolic compounds, 32.17±1.12 mg EAG g sample -1 for FRAP, and 40.76±2.81 μg mL -1 for the capacity of DPPH radical capture when evaluating the crude rosemary extract. This extract was produced by the processes of grinding the leaves, extraction with solvent, and concentration of the extract.…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…This variation in the results can be explained by different concentrations of rosmarinic acid and diterpenes (carnosic acid and carnosol) in the extracts that were analyzed, which might be due to the soil and climatic conditions where rosemary was cultivated, as well as post-harvest conditions and methods of extracting active compounds from the plant (Del Ré & Jorge, 2012). In fact, a large variability is observed among the results of total phenolic compounds content in published articles (Martínez et al, 2019;Pereira et al, 2017;Saini et al, 2020). Moreover, commercial rosemary extract undergoes purification steps to remove flavoring compounds such as monoterpenes, which can impact the sensory profile of the products (Amaral et al, 2018;Damodaran et al, 2010).…”
Section: Antioxidant Activitymentioning
confidence: 99%